The Influence of Product Quality, Social Media Marketing, and Brand Ambassador on Online Buying Decisions - Yulia Cahya Ningrum; Kristina Anindita Hayuningtias (Almana : Jurnal Manajemen dan Bisnis, 2022)
The never-ending pandemic has had a major impact on the world, one of which is the increasing change in consumer behavior to shop online. This makes business people make innovations in leading progress to promote purchase offers including by developing better quality goods, promoting goods that can attract buyers online through social media marketing, and involving a brand ambassador who can do business product marketing in buying decisions. The purpose of this research is to find out how the influence of product quality, social media marketing, and brand ambassadors in determining buying decisions. The approach used on t observation is a purposive sampling approach buying acquiring a sample of one hundred ten respondents and spreading the survey via Google paperwork using a Likert scale. This has a look at uses multiple linear regression tests, t-tests, and F check evaluation, the outcomes received on this take look implying that the product quality variable has a nice and great impact on online buying decisions. even as the social media advertising variables do not affect purchasing choices, the brand ambassador variable indicates a tremendous and giant influence on buying decisions.